Auditing in agricultural sales cooperatives and unions - SAIME ÃUNCE; NURCAN TURAN (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research examines how independent audit principles can help agricultural sales cooperatives in Turkey with their controlling issues. This research examines the potential contributions of an independent audit, which was implemented to ease the burden of auditing agricultural sales cooperatives and unions in Turkey.Method: This research relied on secondary sources of information such as existing literature reviews and relevant pieces of legislation. The Ministry of Commerce’s